Study on The Properties of Bamboo Fibre-Containing Concrete Due to Strength - Hisham, Nurin Natasya; Abdul Rahman, Ts. Mohd Fahmi (Progress in Engineering Application and Technology, 2022)
Concrete constructions are durable. Substandard environmental conditions contribute to concrete building cracks, reducing their durability. Despite its widespread usage in construction, concrete has limited strength, poor impact strength, and cracking. As concrete’s strength increases, its ductility is thought to decrease, however the opposite is the case in several structural applications. This study was conducted to investigate the workability of concrete in order to increase its strength rate. Apart from that, the objective of this study is to ascertain the mechanical and physical properties of bamboo fibre when mixed with Portland cement. This study analysed the structural value of bamboo fibre in a blended Portland cement, taking into consideration its appropriateness for concrete. Bamboo fibres at 1%, 2%, and 3% were utilised as an additive in 1:0.75:1.5 concrete mixes. The concrete grade employed was M30. The workability of the mix was assessed by slump; the cement was subjected to a conventional consistency test. This demonstrates that the workability of normal concrete is medium, that the slump value is 68.58mm, and that the actual slump is a form of slump. Compressive strength was determined at 7days, 14days, and 28days for hardened cured (150 x 150 x 150) mm concrete cubes and the result for 0.1% sample is 26.37MPa, which is a little drop from the strength of the control sample, which is 33.83 MPa. Additionally, the rate at which bamboo fibre concrete absorbed water climbed steadily between 0.1%, 0.2% and 0.3%. Following this, thermal conductivity testing, which is important in determining the level of heat transfer in concrete through conduction, which may lead to cracking and show that 0.2% of additive bamboo fibre in concrete have the density 2009.46 kg/m3 and the thermal conductivity is 0.177(W/m℃).